Naturalist intelligence: effects on critical thinking and needs for cognition (2020)
A pedagogical program based on the improving of naturalist intelligence on the development of critical thinking skills and needs for cognition in fourth-grade students of a public school in Bogotá is analyzed. The study involved 99 students belonging to three intact groups: two of them are experimental and one is the control group. The methodology follows the quantitative approach. The differences of groups were contrasted through the Student's t-test. Moreover, the relation between variables was determined from the Spearman correlation coefficient, ρ [rho]. As instruments for the collection of information, both the Halpern HCTAES test and the need for cognition test were used, with measurement in two moments: one before the experimental treatment—pre-test—and the other one once the training program in naturalist intelligence finished—post-test. The intervention adopted as a pedagogical approach was the problematic teaching proposed by Majmutov. The results show changes in both the experimental and the control groups. They also show a positive correlation between the variables considered: training in naturalist intelligence and the increase in critical thinking skills; as well as their relation with the previous existence of needs for cognition.